Chinese Herbal Bath Therapy for the Treatment of Knee Osteoarthritis: Meta-Analysis of Randomized Controlled Trials. (21st September 2015) - Chen, Bo; Zhan, Hongsheng; Chung, Mei; Lin, Xun; Zhang, Min; Pang, Jian; Wang, Chenchen
Abstract : Objective . Chinese herbal bath therapy (CHBT) has traditionally been considered to have analgesic and anti-inflammatory effects. We conducted the first meta-analysis evaluating its benefits for patients with knee osteoarthritis (OA). Methods . We searched three English and four Chinese databases through October, 2014. Randomized trials evaluating at least 2 weeks of CHBT for knee OA were selected. The effects of CHBT on clinical symptoms included both pain level (via the visual analog scale) and total effectiveness rate, which assessed pain, physical performance, and wellness. We performed random-effects meta-analyses using mean difference. Results . Fifteen studies totaling 1618 subjects met eligibility criteria. Bath prescription included, on average, 13 Chinese herbs with directions to steam and wash around the knee for 20–40 minutes once or twice daily. Mean treatment duration was 3 weeks. Results from meta-analysis showed superior pain improvement (mean difference = −0.59 points; 95% confidence intervals [CI], −0.83 to −0.36;p < 0.00001 ) and higher total effectiveness rate (risk ratio = 1.21; 95% CI, 1.15 to 1.28;p < 0.00001 ) when compared with standard western treatment. No serious adverse events were reported. Conclusion . Chinese herbal bath therapy may be a safe, effective, and simple alternative treatment modality for knee OA. Further rigorously designed, randomized trials are warranted.